FACTORS THAT INFLUENCE GENERATION Z'S FINANCIAL BEHAVIOR - Lies Handrijaningsih; Astried Permanasari; Destik Ayu Wulandari (Universitas Gunadarma, 2025)
Financial behavior for some individuals is currently a problem, especially for some groups in generation Z. This is because amidst increasingly rapid technological developments, of course there will be a change in behavior related to their financial behavior. The aim of this research is to analyze the influence of financial literacy, self control, financial attitudes and income on the financial behavior of generation Z in Indramayu City. The analytical method in this research uses quantitative primary data. The test stages carried out include the research instrument test (validity and reliability test), classical assumption test, multiple regression analysis, F test, T test, and coefficient of determination test (R2). Data collection was carried out by distributing online questionnaires via Google Forms and there were 140 respondents. The sampling technique used was simple random sampling. Testing tools using SPSS software. The results of this research show that the variables financial literacy, self control, financial attitudes, and income simultaneously influence the financial behavior of generation Z in Indramayu City. The variables financial literacy, self control, financial attitude, and income partially influence the financial behavior of generation Z in Inramayu City, and the variable that most dominantly influences the financial behavior of generation Z in Indramayu City is the financial attitude variable.